Health financing: does governance quality matter? - Sirag, Abdalla; Mohamed Nor, Norashidah; Raja Abdullah, Nik Mustapha (Faculty of Economics, University of Tehran, 2017)
This paper contributes to the existing literature by examining the determinants of health financing in 177 developed and developing countries. The study introduces the variables of government effectiveness and control of corruption to capture the impact of governance quality on different mechanisms of health financing. Utilisng panel data analysis, namely system-GMM estimators, to obtain unbiased estimates, the results indicate that public and private health financing do not follow the same pattern. In addition, the GDP per capita and total government expenditure is crucial factors that affect health financing in both developed and developing countries. External aid tends to reduce public health financing, especially when it is received by a country with low governance quality. Interestingly, a high level of government effectiveness and control of corruption are found to be very influential in stimulating public health financing and helping to reduce private health financing in developed countries. However, the low amounts of health financing in developing countries are attributable to the low quality of governance, which increases out-of-pocket health financing.